PROSES KERJA MESIN STRESSING SIMULTAN (MSS) PADA PRODUK TIANG PANCANG TIPE MIDDLE PILE DIAMETER 500 MM DI PT WIKA BETON PPB MAJALENGKA - Hidayat, Adam; Koswara, Engkos (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
Simultaneous Stressing Machine is one of the stages in the prestressed concrete process, namely by providing tension on the steel wire (PC Bar or PC Wire) to overcome the weakness of concrete in withstanding tensile force. The purpose of this study focuses on the working stages of the stressing machine and the calculation of mechanical parameters. The work process of the simultaneous stressing machine consists of several stages starting from preparation, machine inspection, rod installation to the MSS, parameter input, stressing process, and technique and quality. The results of mechanical parameters such as tensile force, elongation, and strain are measured to evaluate the stressing results. With a tension parameter of 50 bar, the process produces a tensile force of 2,800 N, elongation of 0.055 m, and strain of 0.5%. This study provides technical insight into operating the MSS, supporting improved quality and efficiency in prestressed concrete production.